End of life decisions in heart failure: to turn off the intracardiac device or not?. (March 2017) - Ayach, Bilal; Malik, Amrit; Seifer, Colette; Zieroth, Shelley
Abstract : Purpose of review: Heart failure is a significant public health concern around the world. Implantable cardioverter defibrillators with or without cardiac resynchronization therapy (CRT-D) have proven survival benefit. As patients progress to end-stage disease, management shifts to palliative care, and cardiologists are often confronted with how to best manage these devices. Recent findings: Studies suggest that up to one-third of patients with an implantable cardioverter defibrillator receive painful shocks in the last 24 h of life. Disabling pacing or resynchronization devices may further weaken the heart function and expedite death, particularly if the patient has no underlying ventricular rhythm. Is it ethical or legal to discontinue functions of the implantable device? The discussion and the decision to be made are whether to continue both pacing and tachyarrhythmia therapies, disable tachyarrhythmia therapies while maintaining pacing, or discontinue both. Summary: The decision to disable all or parts of the device function is ultimately up to the patient. To avoid painful shocks near the end of life, it is recommended that tachyarrhythmia therapies be turned off when the patient is being treated palliatively. After informed discussion, withdrawing the resynchronization or pacing device option is also acceptable if requested by the patient regardless of the potential outcomes.